MODEL INTEGRASI SAINS DAN AGAMA DALAM PENGEMBANGAN AKADEMIK KEILMUAN UIN - Mulyono, Mulyono (LP2M IAIN Mataram, 2011)
This article explains the efforts made by Universitas Islam Negeri (UIN/the State Islamic University) to integrate science and religion as a solid foundation for scientific academic institutions. Based on a case study at UIN Sunan Kalijaga, the study shows that the institution develops a new paradigm to terminate the dichotomy of science and religion and to integrate them. This is called an integrated-interconnected paradigm symbolized as âSpider Webâ (Jaring Laba-laba). The former Rector of UIN Sunan Kalijaga, Prof. Dr. H. Amin Abdullah (2001-2010) proposed the idea. This idea contends that religious knowledge and sciences are mutually integrated and interconnected. Integration here means that each field in religion and science can benefit from one another to develop new research areas or studies, without which such an effort can be unsuccessful. The integration thus necessitates interconnection among the disciplines in religion and science.